Study and characterization of ultrashort pulse amplification in erbium-doped fibre amplifiers - Tan, Kwang Yonk. (2009)
High power ultrashort optical pulses have widespread applications in micro fabrications, medicine, military and scientific researches. Techniques for the generation, amplification and manipulation of ultrashort optical pulses have been extensively investigated. Physically, an ultrashort optical pulse can be seen as comprising a large number of frequency components, therefore, when it propagates in the medium, the material dispersion property must be appropriately considered. The same effect must also be considered when an ultrashort optical pulse is amplified by the gain medium, in addition to the material dispersion, the gain dispersion normally also impose serious limitations on the quality of the pulse amplification.